2015
DOI: 10.1055/s-0035-1557410
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis in the Arabian Peninsula: A retrospective study from Oman

Abstract: Acute disseminated encephalomyelitis is typically a monophasic multifocal autoimmune demyelinating disease of the central nervous system, which generally follows a febrile infection or a vaccination. It presents with a variety of clinical features reflecting the multifocal nature of the disease. The study was carried out at Sultan Qaboos University Hospital Oman, which is a tertiary care hospital, to see the pattern in this country. A review of inpatients files? records was done with the diagnosis of acute dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 1 , 6 , 7 However none of our LETM had features of ADEM, though such an association of LETM was seen in children with ADEM, a separate group reported earlier. 8 All the children did not undergo CSF examination. The study was allowed in 11 cases only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 6 , 7 However none of our LETM had features of ADEM, though such an association of LETM was seen in children with ADEM, a separate group reported earlier. 8 All the children did not undergo CSF examination. The study was allowed in 11 cases only.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed in a separate study on ADEM in children and previously reported. 8 Neuromyelitis optica (NMO) is an autoimmune condition affecting optic nerves and spinal cord. Aquaporin-4 antibody damages the optic nerves and spinal cord.…”
Section: Discussionmentioning
confidence: 99%